2022
DOI: 10.1038/s41420-022-00919-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stem cell-derived exosomal microRNA-17-5p inhibits anti-tumor immunity in colorectal cancer via targeting SPOP and overexpressing PD-L1

Abstract: Exosomes are known to transmit microRNAs (miRNAs) to affect human cancer progression, and miR-17-5p has been manifested to exert facilitated effects on colorectal cancer (CRC) progression, while the role of tumor stem cells-derived exosomal miR-17-5p in CRC remains unknown. We aim to explore the effect of CRC stem cells-derived exosomes (CRCSC-exos) conveying miR-17-5p on CRC. The exosomes were isolated from CRC stem cells and identified. HCT116 cells were transfected with speckle-type POZ protein (SPOP) inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In addition to colorectal cancer, the change in miR-21 gene expression is particularly important in other cancers, such as lung, breast, and stomach cancer [ 36 38 ]. The same as our study, other studies, including Huang et al in China [ 39 ], Ibrahiem et al in Saudi Arabia (2020) [ 40 ], and Sun et al in China [ 41 ] the expression level of miR-17-5P gene in CRC patients showed a significant increase. It has been shown that CRC patients’ intestinal microbiota is dominated by opportunistic proinflammatory pathogens such as Fusobacterium.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to colorectal cancer, the change in miR-21 gene expression is particularly important in other cancers, such as lung, breast, and stomach cancer [ 36 38 ]. The same as our study, other studies, including Huang et al in China [ 39 ], Ibrahiem et al in Saudi Arabia (2020) [ 40 ], and Sun et al in China [ 41 ] the expression level of miR-17-5P gene in CRC patients showed a significant increase. It has been shown that CRC patients’ intestinal microbiota is dominated by opportunistic proinflammatory pathogens such as Fusobacterium.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, c-Myb increased miR-145-5p expression and in turn reduced SPOP and regulated PD-L1, leading to suppression of T cell functions and induction of immune escape in esophageal adenocarcinoma cells ( 64 ). Cancer stem cell-derived exosomal miR-17-5p reduced SPOP expression and increased PD-L1 accumulation, leading to suppression of antitumor immunity in colorectal cancer cells ( 65 ). Recently, SPOP was found to increase the movement of PD-1 away from PD-L1 in spatial localization, and enhanced tumor metastasis in cervical cancer ( 66 ).…”
Section: Spop E3 Ligasementioning
confidence: 99%
“…Likewise, MYC proto-oncogene that is commonly dysregulated in human malignancies can induce expression of the hsa-mir-17-92 cluster at the transcriptional level 49 . Hsa-miR-17-5p is involved in EMT, metastasis, tumor cell proliferation, cell cycle progression, cell migration, invasion, and angiogenesis in CRC [50][51][52][53][54][55][56] . Two studies have found that hsa-miR-19b-3p is involved in response to chemotherapy and radiotherapy in CRC 57,58 .…”
Section: Mirnasmentioning
confidence: 99%